1986
DOI: 10.1073/pnas.83.13.4904
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of somatomedins from human fetal brain: identification of a variant form of insulin-like growth factor I.

Abstract: A fetal form of somatomedin (insulin-like growth factor) that crossreacts in the fetal brain radioreceptor assay has been proposed to exist in humans. Using this assay to monitor activity during purification, we have isolated a variant form of insulin-like growth factor I (IGF-I) from human fetal brain tissue. The variant IGF-I showed potent crossreaction in the fetal brain radioreceptor assay and stimulated DNA synthesis in fetal brain cells in vitro. Structural analysis revealed the variant IGF-I to have a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(65 citation statements)
references
References 18 publications
5
59
0
1
Order By: Relevance
“…In adult human cerebrospinal fluid and brain, IGF-II, but not IGF-I, was found (12,13). However, a truncated form of IGF-I as well as IGF-II was recently isolated from fetal and adult human brain (14,15). Evidence for local synthesis in pituitary and brain (13,16) suggests a physiological role for IGF-II as a neuroregulator and/or a brain growth factor.…”
Section: Ipmentioning
confidence: 99%
“…In adult human cerebrospinal fluid and brain, IGF-II, but not IGF-I, was found (12,13). However, a truncated form of IGF-I as well as IGF-II was recently isolated from fetal and adult human brain (14,15). Evidence for local synthesis in pituitary and brain (13,16) suggests a physiological role for IGF-II as a neuroregulator and/or a brain growth factor.…”
Section: Ipmentioning
confidence: 99%
“…Sara et al (21,22) first identified a fetal somatomedin with characteristics different from those of adult IGF and more recently showed, using a fetal brain membrane radioreceptor assay, that circulating IGF levels of human fetuses between 16 and 28 wk of gestation include two components: IGF 2, and a "trun-0.1 1 versus 1.50 f 0.07).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the isolation of a potent, N-terminally truncated form of IGF-I, des-(1-3)-IGF-I, from bovine colostrum , while others have also isolated this protein from human brain (Sara et al 1986, Carlsson-Skwirut et al 1987. Hence, we were interested to know whether such a species exists in kangaroo serum.…”
Section: Discussionmentioning
confidence: 99%